Pregnancy outcomes of patients with retained products of conception following miscarriage treated with relugolix, an oral gonadotropin-releasing hormone antagonist - Sasatsu, Satoko; Ono, Yosuke; Miyashita, Dai; Yoshihara, Tatsuya; Tanaka, Kota; Tada, Yuri; Owada, So; Nakagomi, Akiko; Ikeda, Shoko; Ohgi, Maki; Ogasahara, Eriko; Tagaya, Hikaru; et al. (Frontiers in Medicine, 2026)
BackgroundRelugolix, an oral gonadotropin-releasing hormone (GnRH) antagonist, represents a potentially effective and less invasive therapeutic approach for retained products of conception (RPOC). However, its impact on subsequent pregnancy outcomes remains unclear. This study aimed to evaluate these outcomes following GnRH antagonist treatment for RPOC.MethodsThis single-center cohort study encompassed 20 patients diagnosed with RPOC following miscarriage or abortion before 22 gestational weeks who were treated with oral relugolix, a GnRH antagonist, from January 2022 to July 2024. Following treatment completion and hysteroscopic confirmation of complete resolution, 12 patients subsequently conceived and were prospectively followed for pregnancy and neonatal outcomes. To contextualize outcomes, results were compared with the non-GnRH antagonist group managed at the same institution from 2014 to 2021 without GnRH antagonist exposure.ResultsThe GnRH antagonist group had fewer patients requiring surgical intervention than the non-GnRH antagonist group [30.0% (6/20) vs. 70.1% (54/77), p = 0.002], underscoring the reduced invasiveness of medical therapy. Of the 12 pregnancies following relugolix treatment, 4 led to early miscarriage and 8 progressed beyond 22 gestational weeks. The GnRH antagonist and non-GnRH antagonist groups exhibited comparable clinical pregnancy and live birth rates (53.3% vs. 73.3 and 33.3% vs. 48.9% per embryo transfer, respectively; not significant). Similarly, the interval from RPOC diagnosis in the previous pregnancy to gestational sac confirmation in the current pregnancy (328.9 ± 153.4 vs. 486.9 ± 658.8 days) and the interval from RPOC treatment completion to gestational sac confirmation (295.7 ± 166.6 vs. 445.8 ± 628.2 days) did not significantly differ between both groups.ConclusionRelugolix therapy for RPOC was associated with preserved fertility and favorable pregnancy outcomes comparable to conventional management.